Imaging in-operando LiCoO2 nanocrystallites with Bragg coherent X-ray diffraction - David Serban; Daniel G. Porter; Ahmed H. Mokhtar; Mansoor Nellikkal; Sivaperumal Uthayakumar; Min Zhang; Stephen P. Collins; Alessandro Bombardi; Peng Li; Christoph Rau; Marcus C. Newton (Communications Chemistry)
Abstract Although the LiCoO2 (LCO) cathode material has been widely used in commercial lithium ion batteries (LIB) and shows high stability, LIB’s improvements have several challenges that still need to be overcome. In this paper, we have studied the in-operando structural properties of LCO within battery cells using Bragg Coherent X-ray Diffraction Imaging to identify ways to optimise the LCO batteries’ cycling. We have successfully reconstructed the X-ray scattering phase variation (a fingerprint of atomic displacement) within a  ≈ (1.6 × 1.4 × 1.3) μm3 LCO nanocrystal across a charge/discharge cycle. Reconstructions indicate strained domains forming, expanding, and fragmenting near the surface of the nanocrystal during charging, with a determined maximum relative lattice displacements of 0.467 Å. While discharging, all domains replicate in reverse the effects observed from the charging states, but with a lower maximum relative lattice displacements of 0.226 Å. These findings show the inefficiency-increasing domain dynamics within LCO lattices during cycling.